IMPLEMENTATION OF AN OCCLUSAL WAFER IN SEVERE MANDIBULAR FRACTURE CASES WITH POST-ORIF MALOCCLUSION: A CASE SERIES - Chintia Amelia Pratiwi; Mirnasari Amirsyah; Teuku Nanda Putra (Universitas Airlangga, 2024)
Highlights: This study shows that occlusal wafers can effectively correct malocclusion in patients with segmental mandibular fractures after ORIF plating. Occlusal wafers help reshape the dental arch within 2 to 4 weeks, reduce surgery time, and simplify follow-up care, making them a valuable option for surgeons. Abstract: Introduction: Improper treatment of severe mandibular fractures can lead to malocclusion, which poses a significant challenge for reconstructive surgeons. The occlusal wafer provides an effective solution for managing malocclusion following ORIF plating of maxillofacial fractures during the one-month postoperative evaluation period. Made from acrylic resin, the occlusal wafer serves as an intermediate guide in orthognathic surgery. It helps reposition the maxilla, adjust the mandible, and modify the jawbones to achieve ideal occlusion. The device can reshape the dental arch to any pre-planned position within 2 to 4 weeks. Case Illustration: We present two cases of patients with segmental fractures.Case 1: A 26-year-old male also had segmental fractures of the left angle and right body of the mandible. He achieved occlusion after ORIF plating; however, malocclusion developed during the three-week follow-up. Case 2: A 28-year-old female presented with segmental fractures of the left angle and right body of the mandible. She initially achieved occlusion after ORIF plating, but malocclusion was noted during the one-month follow-up. Discussion: Both of these patients had segmental fractures and experienced malocclusion following ORIF plating, but occlusion was achieved after occlusal wafer installation. Conclusion: The use of an occlusal wafer facilitates optimal occlusion, streamlines the surgical procedure by reducing operating time, and enhances the ease of postoperative monitoring. This approach proves particularly valuable in cases where ORIF plating has been performed yet ideal occlusal alignment remains unachieved.